Adsorption Capacity of Mercury Using Sargassum crassifolium Activated Adsorbent - Imelda H Silalahi; Titin Anita Zahara; Henry Martua Tampubolon (Biopropal Industri, 2012)
This study aims to determine the maximum adsorption capacity of Hg using activated Sargassum crassifolium adsorbent. Sargassum crassifolium was activated by protonation using sulfuric acid (H2SO4) 1 M followed by heating for 24 hours at 100OC. Optimum conditions of adsorption was discovered through various of pH and contact time to the Hg(II) concentration decrease. The analysis showed that the optimum pH was 7 and contact time was 60 minutes. Finally the maximum adsorption capacity of Hg(II) using activated Sargassum crassifolium adsorbent was 2,90 mmol/g determined by Langmuir Isotherm equation.